Marking First Thinnings in Pine Plantations: Potential for Increased Economic Returns - Byron Love; Michael G. Andreu; Chris Demers (EDIS)
This 3-page fact sheet written by Byron Love, Michael Andreu, and Chris Demers and published by the UF/IFAS School of Forest Resources and Conservation summarizes a study to determine whether landowners may gain increased economic returns if they mark the first thinning in a southern pine stand. The study found that marking can indeed bring higher revenue at final harvest. The greater number of high-quality and faster-growing trees remaining after a marked thinning is the main reason for immediate and future increases in value. https://edis.ifas.ufl.edu/fr410